Metode Pembelajaran Metode Inquiry dan Gaya Belajar Terhadap Hasil Belajar Bahasa Inggris - Wawan Gunawan; Abd. Cholid (Departement of Mathematics Education, 2023)
The aims of this study were to find out (1) to test the differences between the Inquiry Method and the conventional method on English Learning Outcomes, (2) To test the differences in learning styles on English Learning Outcomes, and (3) To test the effect of the interaction between the Inquiry Method and the Inquiry Method conventional and learning styles on English Learning Outcomes. This quantitative research uses the experimental method. The data analysis technique in this study was a two-way analysis of variance test using SPSS 25. The research design used was a 2x3 factorial design. Based on the results of the data analysis are: (1) Application of the Inquiry Method and Convention Method with a significance value of less than α <0.05, namely 0.000, so that it can be explained that there are differences in the English Learning Outcomes of class VII students of SMPN 48 Surabaya who are taught using Inquiry and Direct Instruction Methods, (2) Audio, Visual and Kinesthetic Learning Styles of students with a significance value of less than α <0.05, namely 0.000, meaning that there are differences in the English Learning Outcomes of class VII students of SMPN 48 Surabaya, and (3 ) the inquiry interaction method and the convention method with a significant value less than α <0.05, namely 0.001, so that there is an interaction between the inquiry method and the convention method and the Audio, Visual and Kinesthetic Learning Styles on the English Learning Outcomes of Class VII students of SMPN 48 Surabaya. Based on the results of this study, it was concluded that using the Inquiry Method and Learning Styles could improve English Learning Outcomes. The implication of this research is that the Inquiry Method can be used as a way to improve English learning outcomes.